Employee engagement: a literature review: Keterlibatan karyawan: penelusuran literatur - Chairunnisa,; Aji, Fatwa; Wijaya, Andre Nugraha (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This systematic study aims to examine the research results on employee engagement, provide a comprehensive overview of employee involvement, and explore concepts. Methods: The research method used here is a literature review using journals from both national and international through accredited databases such as Google Scholar, ScienceDirect, Scopus, and Garuda. The search used secondary data from February 14th to May 8th, 2023. Using the keywords employment, AND work AND engagement AND of AND employees. Results: Employee engagement is very influential to the company's progress; when employees do not have work engagement, employee engagement will reduce the goals and profits obtained from a company. Factors that can influence are perceived organizational support, work-family enrichment, tenure, job resources, personal resources, and others. Employees feel that they can stay focused and concentrate on the work even though it is heavy, feel that what they are doing is noble work, and enjoy very intense work. This literature study is expected to serve as a basis for further study of work attachments and other relevant variables.